Winter warm-up frequency and the degree of temperature fluctuations affect survival outcomes of spotted-wing drosophila winter morphotypes. (May 2021) - Stockton, Dara G.; Loeb, Gregory M.
Graphical abstract: Highlights: Temperature fluctuations affect the biology and cold tolerance of insects. We tested the effects of temperature changes on the survival of SWD. At mild temperatures (5 °C), increasing warm-up frequency was harmful. At freezing temperatures (0 °C), daily warm-ups improved survival outcomes. Fluctuating temperatures during cold acclimation similarly improved survival. We conclude temperature fluctuations may affect overwintering survival of SWD. Abstract: Among overwintering Drosophila suzukii, discrete environmental changes in temperature and photoperiod induce a suite of biochemical changes conferring cold tolerance. However, little is known regarding how temperature fluctuations, which can influence metabolic and cellular repair activity, affect survival outcomes in this species. For that reason, we designed three experiments to test the effects of intermittent warm-up periods and the degree of temperature fluctuation on winter-morphotype (WM) D. suzukii survival. We found that at 5 °C, a temperature sufficient to induce reproductive diapause, but warm enough to allow foraging, increasing warm-up frequency (warmed to 25 °C at various interval schedules) was associated with decreased survival. In contrast, when the nightly low temperature was 0 °C, daily fluctuations that warmed the environment to temperatures above freezing (5, or 15 °C) appeared beneficial and resulted in improved survival compared to flies held at 0 °C during day and night. When we next evaluated cold tolerance using a 24-hour stress test assay (-5 °C), we found that again, thermal fluctuations improved survival compared to static freezing conditions. However, we also found that WM D. suzukii exposed to freezing temperatures during acclimation were less cold tolerant, regardless of the thermal fluctuation schedule, indicating that there may be tradeoffs between adequate acclimation temperature, which is required to induce cold tolerance, and the ensuing effects of incidental chill injury. Moving forward, these data, which account for the nuanced interactions between the thermal environment and in the internal physiology of D. suzukii, may help refine seasonal populations models, which aim to forecast pest pressure based on conditions the previous winter.